Aircraft Level Thermal Management Analysis for Early Design Stages of Future Aircraft: Integration of Systems and Compartments into an Interacting Generic Approach - Muijden, J. van; Aalbers, V.J.E. (MDPI, 2025)
For future commercial aircraft having hybrid electric drivetrains, the impact of electrical power generation and distribution on heat production and required heat rejection is of a larger magnitude than for conventional aircraft. The thermal management system (TMS) to control component and compartment temperatures may require dedicated solutions. The impact of TMS on top-level aircraft requirements (TLARs), e.g., weight and drag penalties, should become clear in the early stages of design for integration in the configuration. To assess this impact, a generic approach is presented to support aircraft level thermal management analysis and design based on global aircraft parameters.